Ovarian and cervical cancer awareness: development of two validated measurement tools. Issue 3 (20th September 2011) - Simon, Alice E; Wardle, Jane; Grimmett, Chloe; Power, Emily; Corker, Elizabeth; Menon, Usha; Matheson, Lauren; Waller, Jo
Abstract : Background: The aim of the study was to develop and validate measures of awareness of symptoms and risk factors for ovarian and cervical cancer (Ovarian and Cervical Cancer Awareness Measures). Methods: Potentially relevant items were extracted from the literature and generated by experts. Four validation studies were carried out to establish reliability and validity. Women aged 21–67 years ( n =146) and ovarian and cervical cancer experts ( n =32) were included in the studies. Internal reliability was assessed psychometrically. Test-retest reliability was assessed over a 1-week interval. To establish construct validity, Cancer Awareness Measure (CAM) scores of cancer experts were compared with equally well-educated comparison groups. Sensitivity to change was tested by randomly assigning participants to read either a leaflet giving information about ovarian/cervical cancer or a leaflet with control information, and then completing the ovarian/cervical CAM. Results: Internal reliability (Cronbach's α=0.88 for the ovarian CAM and α=0.84 for the cervical CAM) and test-retest reliability ( r =0.84 and r =0.77 for the ovarian and cervical CAMs, respectively) were both high. Validity was demonstrated with cancer experts achieving higher scores than controls [ovarian CAM: t (36)= –5.6, p <0.001; cervical CAM: t (38)= –3.7, p =0.001], and volunteers who were randomised to read a cancer leaflet scored higher than those who received a control leaflet [ovarian CAM: t (49)=7.5, p <0.001; cervical CAM: t (48)= –5.5, p <0.001]. Conclusions: This study demonstrates the psychometric properties of the ovarian and cervical CAMs and supports their utility in assessing ovarian and cervical cancer awareness in the general population.